Risk of a coronary event in patients after ischemic stroke or transient ischemic attack - Poledník, Ivan; Sulzenko, Jakub; Widimsky, Petr (Anatolian journal of cardiology, 2021)
Coronary artery disease (CAD) together with stroke are the leading causes of death worldwide, and together, they pre-sent a health and economic burden. Ischemic stroke survivors and patients who suffered transient ischemic attack (TIA) have a higher prevalence of coronary atherosclerosis, and they have a relatively high risk of myocardial infarcti-on and nonstroke vascular death. Pubmed was searched for studies focused on investigating coronary atherosclerosis in ischemic stroke survivors or patients who suffered TIA and their cardiovascular risk assessment. There were corona-ry plaques in 48%-70% of stroke survivors without a known history of CAD, and significant stenosis of at least one coronary artery can be found in 31% of these patients. CAD is a major cause of morbidity and mortality in stroke survivors. Detection and treatment of silent CAD may improve the long-term outcome and survival of these patients.
Keywords: rizikové faktory; cévní mozková příhoda; Humans; Risk Factors; lidé; tranzitorní ischemická ataka; ischemická cévní mozková příhoda; Stroke; Ischemic Attack, Transient; Ischemic Stroke; Brain Ischemia; ischemie mozku